Supplier Selection Using Analytic Hierarchy Process: An Application From Turkey - Ozkan, Betul; Basligil, Huseyin; Sahin, Nergis (INT ASSOC ENGINEERS-IAENG, 2011)
Decision making is one of the most important activities in companies. Making the right decisions have an important effect on companies' profit and success. In this paper our purpose is to choose the best supplier for computer and printer purchasing for General Directorate of Land Registry. We use Analytic Hierarchy Process (AHP) for selection methodology. First of all, we determine our main and sub-criteria. We have 4 main criteria and 16 sub-criteria. Our potential suppliers are A, B and C. Then we apply AHP on our problem and finally we determined the best supplier.
Keywords: AHP; computer and printer purchasing; decision making; supplier selection; MODEL; INDUSTRY; Computer Science; Engineering